Semiotic narratology: the "point of view" question - Nadal, José María (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The paper defends a General Narratology ―valid for any substance and form of expression and for any genre or type of discourse, artistic or not― integrated in a General Semiotics Theory to keep the scientific criterion of coherence, to generate each one of the components of the theory and the object analyzed from others, etc. The author separates the scope of enunciation from that of discursivization; and the instances of enunciation from those of discursivization and those of implicit enunciation. The first ones do not exist in the statement; the second ones can be made explicit in it; the third ones, never, and yet, exist in it.On the contrary to what is held by most researchers, the paper states that there are morphemes of "visual" expression ―motivated (non-arbitrary) of bidimensional perspectiva artificialis― specialized in the roles of discursivizer subjects. In the "visual" expression, on the contrary to the usual practice, the author opposes the "visual" discursivizer ―or perspectivizer or plasticizer or imageur or "visual narrator", located in the Origin of the Perspective― the appreciator ―the "focalizator" , the person in charge of the "point of view", the one that assumes as responsible the predicate (according to him, it is like that), but not the production of the discourse―.Based on this distinction, the paper describes in an original way phenomena such as those of indirect and free indirect discourse, identifies them in the "visual" expression ―photographic, cinematographic― and dissociates radically the opposition between non-direct discourse and direct discourse, from the opposition, different, between non-indirect and indirect discourse.
Keywords: Semiotics; Narratology; point of view; discourse